2022
DOI: 10.3390/nu14071426
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Prevalence of Micronutrient Imbalances in a Dutch General Population Cohort and the Effects of a Digital Lifestyle Program

Abstract: Maintaining an adequate micronutrient status can be achieved by following a complete, diverse diet. Yet, food trends in Western countries show suboptimal consumption of healthy nutrients. In this study, we explored the prevalence of vitamin and mineral imbalances in a general population cohort of Dutch adults and evaluated the effect of a digital lifestyle program on the nutritional status and nutrition health behaviors of these individuals. A micronutrient panel was measured in 348 participants, alongside a d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A survey of 400 Dutch children aged 6 months–3 years found iron deficiency in 19% [ 29 ]. Iron deficiency was also seen in 9% of 376 Dutch and migrant elderly [ 30 ] and 4% of healthy adults, with a higher prevalence of iron deficiency in women, in a study of 348 users of a digital lifestyle program [ 31 ]. Thus, the large proportion of inadequate intakes in toddlers is likely to contribute to iron deficiency in toddlers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of 400 Dutch children aged 6 months–3 years found iron deficiency in 19% [ 29 ]. Iron deficiency was also seen in 9% of 376 Dutch and migrant elderly [ 30 ] and 4% of healthy adults, with a higher prevalence of iron deficiency in women, in a study of 348 users of a digital lifestyle program [ 31 ]. Thus, the large proportion of inadequate intakes in toddlers is likely to contribute to iron deficiency in toddlers.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a lack of data on folate status in the Netherlands, in a study of 348 healthy adults, folate deficiency was found in 14.1% [ 31 ]. No established biomarkers exist for calcium, therefore the impact of low calcium intakes can only be tracked through the prevalence of diseases related to calcium intakes, such as osteoporosis.…”
Section: Discussionmentioning
confidence: 99%